Moral Message In The Web Series Little Mom Film - Zahkya Lestari; Vethy Octaviani; Yanto Yanto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research aims to find out the moral message contained in the Web Series film "Little Mom". Testing in this research uses descriptive qualitative methods using a semiotic analysis approach. The subjects in this research are pieces of images and narration/dialogue contained in the Web Series film "Little Mom" which relate to moral messages regarding education for society in everyday life. The analysis used is semiotic analysis using the Charles Sanders Pierce approach which consists of 3 levels of sign, namely sign, object and interpretant. The results of the research show that the moral message in the Little Mom Web Series film is don't do something beyond your limits but think about the consequences, have the courage to take responsibility for mistakes you have made, such as aborting a pregnancy, and the role of the family which is very necessary if things like this happen. The Little Mom Web Series film occurred, as a society it is better not to discriminate, this can affect the psychology of the perpetrator and the final moral message is that a real man will accept and respect his partner, not take away honor for the sake of momentary lust.